Prevalence and patterns of tobacco use among young adults in India - does perceived stress play a role? - Khurana, Poornima; Banerjee, Rupsa (International Journal Of Community Medicine And Public Health, 2024)
Background: Tobacco use among young people is a public health concern. Perceived stress among young adults as a determinant for tobacco use has not been extensively explored previously in India. Methods: A cross-sectional study was conducted among young adults aged 18-30 years across India. Data was collected using a self-administered, web-based, online questionnaire, on sociodemographic characteristics, tobacco use and its pattern, and the levels of perceived stress using the Perceived Stress Scale (PSS-10). Results: The prevalence of tobacco use in our study sample was 25.7% and the mean age at initiation of tobacco use was 20.71 years. Though tobacco use was significantly associated with male gender [aOR=2.26 (1.16-4.38), p=0.01], current alcohol consumption [aOR=13.73 (6.72-28.04), p=0.00] and having known smokers among family and friends [aOR=3.13 (1.39-7.04), p=0.01], there was no association between levels of perceived stress and tobacco use. Cigarettes/beedis were the most commonly used tobacco product, 27.58% of respondents reported using tobacco products daily or for more than half the days of the week and 48.27% of respondents started using tobacco out of curiosity. Seventy percent of users used tobacco during specific events like social gatherings and vacations while 57.47% used tobacco while meeting specific colleagues/ friends. Conclusions: We found no association between perceived stress and tobacco use. However, current use of alcohol and having knowledge about smokers among family and friends significantly determined tobacco use among our study population. This necessitates more holistic approaches towards behaviour change efforts for tobacco control.